2006
DOI: 10.1111/j.1468-3083.2006.01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in mild to moderate acne: relationship to clinical severity and factors influencing change with treatment

Abstract: The effects of acne vulgaris on quality of life and changes in quality of life after treatment are not only explainable by objective severity of acne. Patients' and clinicians' judgements about acne severity are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
69
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 29 publications
18
69
1
8
Order By: Relevance
“…Based on obtained information there was a significant relation between patients quality of life score and gender so that women had higher scores in quality of life suggested a disorder in patients quality of life same results obtained in Baghestani's et al study in Bandar -Abbas also in Bernz's et al study on 479 affected patients to acne and in Cabaler's et al These findings indicated that acne can affect women's psycho-social position more than men (3,8,14). Despite studies, there is no significant relation between gender and quality of life in Vaker's et al study on 200 adult affected patients and also in Malon's et al study on 111 affected patients to acne (11,12).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Based on obtained information there was a significant relation between patients quality of life score and gender so that women had higher scores in quality of life suggested a disorder in patients quality of life same results obtained in Baghestani's et al study in Bandar -Abbas also in Bernz's et al study on 479 affected patients to acne and in Cabaler's et al These findings indicated that acne can affect women's psycho-social position more than men (3,8,14). Despite studies, there is no significant relation between gender and quality of life in Vaker's et al study on 200 adult affected patients and also in Malon's et al study on 111 affected patients to acne (11,12).…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand there is a significant relation between disease and quality of life, so that people who have more severe disease, had higher quality of life scores suggesting quality of life disorder. There is no significant relation between acne severity and quality of life in Matsoka's et al study, but there is a significant relation between lesions severity and patients quality of life in Hong's et al study, in Cobaler's et al study and in Yazirey's et al study (14)(15)(16)(17). Patients who have more severity had higher scores in quality of life they have reported more anxiety and depression.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There is no precise information about whether there is a relationship between personality and the development of acne (11). Some authors suggest that people with acne have unstable, neurotic traits such as avoidant personality traits; however, other authors have suggested that acne should be treated as an organic event and that personality traits have no effect on the development of acne (12,13).…”
Section: Discussionmentioning
confidence: 98%
“…Acne is a disease of the pilosebaceous unit and affects more than 80% of the general population in their lifetime [1]. It is believed to be a disease of the adolescence and is generally self-limiting.…”
Section: Introductionmentioning
confidence: 99%